The microstructure and photoluminescence of ZnO–MoS2 core shell nano-materials. (30th January 2017) - Yu, H; Liu, C M; Huang, X Y; Lei, M Y
Abstract: In this paper, ZnO–MoS2 -FT (FT is the fabrication temperature of MoS2 ) core shell nano-material samples (with ZnO as a core and MoS2 as a shell material) were fabricated on ITO substrate using hydrothermal method. The crystal structure, morphology, optical absorption and photoluminescence (PL) of samples were investigated. Compared with that of pure ZnO nanorods, ZnO–MoS2 -FT samples show an enhanced light absorption. In addition, ultraviolet (UV) and visible (Vis) PL intensity of ZnO–MoS2 -FT samples excited by 325 nm laser are greatly weakened. The UV PL peak position is not changed obviously. However, the Vis PL peak position is changed visibly. The Vis PL of ZnO–MoS2 -FT samples under UV excitation indicates that the ratio of oxygen interstitial to oxygen vacancy is decreased. The suppression of UV PL of ZnO–MoS2 -FT samples may be related to the weakening of crystal quality of ZnO, easier separation of electron–hole pairs, enhancement of light absorption, and newly introduced defects in the interface between ZnO and MoS2 . Under 514 nm laser excitation, the PL peak position of ZnO–MoS2 -FT samples has a red shift with FT being increased from 80 to 160 °C. The influence of excitation power (EP) on the PL of ZnO–MoS2 -FT samples was also investigated. The PL of ZnO–MoS2 -FT samples have a red shift with EP being increased. This may be due to the sample temperature is increased with EP, resulting an enhancement of electron–phonon interaction. A schematic diagram of charge generation and transfer is presented to understand the mechanism of PL of ZnO–MoS2 under UV and Vis excitation.